1997
DOI: 10.1093/hsw/22.1.20
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Integration of Social Work Psychosocial Services into Rural Primary Care Practice

Abstract: This article argues for health and mental health collaboration between social workers and rural primary care physicians and describes a study of physicians' attitudes toward integrated services. The physicians who expressed interest in a collaborative arrangement differed in practice characteristics, attitudes toward social workers, and endorsement of social work roles. Also, interested physicians treated significantly more patients, had the lowest proportion of patients over age 65, and endorsed as useful a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Previous studies on physician perceptions of challenges in integrating the social worker within the primary care setting have revealed mixed findings. In a study to assess physicians' attitudes toward the potential roles for social workers in a primary care setting, Badger, Ackerson, Buttell, and Rand (1997) found that fewer than half of the providers interviewed reported that social workers could conduct screening or provide therapy for mental health disorders, or that social workers could have a role in preparing patients for hospitalizations and the accompanying life changes with this type of admission. Alternately, Netting and Williams (1996) found that physicians voiced concerns that collaborating and coordinating care with social workers located in their office will take up too much of their time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on physician perceptions of challenges in integrating the social worker within the primary care setting have revealed mixed findings. In a study to assess physicians' attitudes toward the potential roles for social workers in a primary care setting, Badger, Ackerson, Buttell, and Rand (1997) found that fewer than half of the providers interviewed reported that social workers could conduct screening or provide therapy for mental health disorders, or that social workers could have a role in preparing patients for hospitalizations and the accompanying life changes with this type of admission. Alternately, Netting and Williams (1996) found that physicians voiced concerns that collaborating and coordinating care with social workers located in their office will take up too much of their time.…”
Section: Discussionmentioning
confidence: 99%
“…While there is growing evidence that primary care physicians and nurses recognize that having social workers available to address psychosocial and environmental aspects of illnesses would enhance their practice (Golden & Iris, 2005;Rock & Cooper, 2000;Sommers et al, 2000), addressing providers' hesitations to integrating social workers is likely to be one of the greatest obstacles to developing more collaborative care models in primary care. Additionally, a number of studies have found that physicians and nurses do not fully understand roles of social workers, suggesting the importance of provider education if these collaborations are to be successful (Netting & Williams, 1996Badger, Ackerson, Buttell, & Rand, 1997).…”
Section: Background and Significancementioning
confidence: 99%
“…Research has also focused on the similarities between social workers and other medical professionals Kadushin, 1997, 1995) and the perceptions of social workers of other medical professionals (Abramson and Mizrahi, 1994;Badger et al, 1997;Csikai and Sales, 1998;Netting and Williams, 1996). There are differing views as to what social workers do in the hospital and the ways in which they perceive their role, compared with how other medical professionals view the social work role Lefcowitz, 1992, 1995;Egan and Kadushin, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of trust, communication and educational awareness were consistently found in the results of research studies when acknowledging the conflicts that arose throughout interprofessional collaboration. Additionally, the lack of teamwork skills led to the struggle of relinquishing leadership and power which was also a common finding in the results of various research studies (Abramson and Mizrahi 1996;Badger et al 1997;Kainz 2002;McMinn et al 2003McMinn et al , 1998Mizrahi and Abramson 2000;Williams et al 1978).…”
Section: Understanding Interprofessional Collaborationmentioning
confidence: 94%